Optimization of Citrus limon peel extraction, determination of main chemical components and effectiveness in repellency against Aedes mosquito dengue fever vector - Hue, Phung Thi Kim; Van Loc, Tran; Tri Vien, Le; Dung Sy, Le; Viet Hieu, Ho; Nhung, Le Thi; Thanh Do, Le; Khoa, Pham Thi (Vietnam Journal of Biotechnology, 2022)
Currently, scientific publications are focusing on the pharmacological actions of Citrus limon's extract and essential oil. Its essential oil is rich in bioactive monoterpenoids, such as D-limonene, β-pinene, γ-terpinene. Citrus limon essential oils have been recognized as the potential source of natural insecticides because of their selectivity, ability to be biologically degraded into non-toxic compounds, low impacts on biodiversity and the environment. Many previous studies have reported anti-bacterial, anti-fungal, anti-inflammatory, anti-cancer, hepato-regenerative, and cardio-protective activities of Citrus limon essential oil. In this study, we collected the discarded Citrus limon peel source in Gia Lai province to utilize as a material to build an optimized extraction process with the following criteria: extraction solvent, solvent/sample ratio, extraction temperature, and extraction time. The results showed a stable extraction process with a maximum extraction efficiency of 4.02%, at 40°C, for 3 hours, with two extraction times using 95% ethanol for solvent. Using GC/MS method, the determined limonene content accounted for 12.2% of the extract. The Citrus limon peel extract exhibited potency against Aedes aegypti (arbovirus vector) at a concentration of 0.01 mL, with protection time of 70 minutes and biting percentage of 0.9%, compared to negative control with statistically significant (P < 0.05). The above results correspond with the most recent publications about the effects of mosquito repellence of certain plant-based essential oils. This study has proven that Citrus limon peel in this locality signifies a promising candidature for future studies regarding its main active compound, limonene, in the control of dengue-transmitting vectors. Therefore, Citrus limon peel extract brings hope to develop new mosquito repellency products in the future.